Post your question in the Comment section below, and a GRE expert will answer it as fast as humanly possible.

- Video Course
- Video Course Overview
- General GRE Info and Strategies - 7 videos (free)
- Quantitative Comparison - 7 videos (free)
- Arithmetic - 42 videos
- Powers and Roots - 43 videos
- Algebra and Equation Solving - 78 videos
- Word Problems - 54 videos
- Geometry - 48 videos
- Integer Properties - 34 videos
- Statistics - 28 videos
- Counting - 27 videos
- Probability - 25 videos
- Data Interpretation - 24 videos
- Analytical Writing - 9 videos (free)
- Sentence Equivalence - 39 videos (free)
- Text Completion - 51 videos
- Reading Comprehension - 16 videos

- Study Guide
- Philosophy
- Office Hours
- Extras
- Prices

## Comment on

Solving Age Questions## It is accurate, yet a very

## I used one variable, starting

Then I solved for 3i + 11 + 2, which gave me 28.

Would this approach translate into other problems, using one variable but starting with the simplest set of variables, even if it's starting in the past?

## You're referring to the

You're referring to the question that starts at 3:05 in the video.

Yes, that strategy also works. As long as your variable expressions match the given information, your approach will work.

You'll see that we used 1 variable to solve the first questions and 2 variables to solve the second question. I let students decide what works best for them. The 2-variable approach requires us to solve a system of equations, and the 1-variable approach can result in equations/expression that are more complex, but both approaches will work.

## hello, Can you add how to do

## Glad to help!

Glad to help!

Let x = Abbie's PRESENT age

So, 42-x = Iris' PRESENT age

This means that....

x-11 = Abbie's age 11 YEARS AGO

42-x-11 = Iris' age 11 YEARS AGO

Simplify to get: 31-x = Iris' age 11 YEARS AGO

Given: 11 years ago, Abbie was 3 TIMES as old as Iris

We can write: Abbie's age 11 years ago = 3(Iris' age 11 years ago)

So we get: x-11 = 3(31-x)

Expand: x - 11 = 93 - 3x

Add 3x to both sides: 4x - 11 = 93

Add 11 to both sides: 4x = 104

Solve: 4 = 26

So, Abbie's PRESENT age = 26

So, Abbie will be 28 years old IN TWO YEARS

## thx Brent for ur quick answer

thank you Brent for everything.... u really into math and u likes it, and that gives u this gift to explain it v easily.

## Thanks AFNAN!

Thanks AFNAN!

## Hi Brent, Is below

Let 42-I = Abbie's PRESENT age

So, I = Iris' PRESENT age

I-11 = Iris' age 11 YEARS AGO

42-I-11 = Abbie's age 11 YEARS AGO

Simplify to get: 31-I = Abbie's age 11 YEARS AGO

Given: Abbie's age 11 years ago = 3(Iris' age 11 years ago)

31-I = 3(I-11)

31-I = 3I - 33

64 = 4I

I = 16

Abbie's age = 42 - I = 42 -16 = 26

So, Abbie's PRESENT age = 26

So, Abbie will be 28 years old IN TWO YEARS

## Perfectly executed!

Perfectly executed!

## Great.Thanks Brent for

## Hi Brent,

I solved this by testing answer choice

For 1st Question type

I took Soo present age = 12(Option C)

Hence marco age = 4(since Soo is 8yrs older)

Then in 4 yrs Soo age = 16 & Macro = 8(Now Soo age will be twice of macro from the question is satisfied) hence option C is correct.

For 2nd Question

I again took option C for Abbies age = 18(2 yrs from now) Current age of Abbies = 16

Hence Iris presnt age = 26 (sum of age is 42)

but we need abbies to be greater than Iris(condition from question)

Hence option C is incorrect also Option A&B cancel out.

Now I took option E i.e = 28

using the same approach

Abbie present age = 26

Iris age = 16 ( sum of age = 42)

after 11 yrs abbie age wil be = 15 & Iris age = 5

i.e abbie age is 3 time as old as Iris ( 5*3 = 15)

Hence option E correct answer.

Is this approach correct & will It work for all similar age questions.

I just tried bcz u said in 1st video of this section that testing option should be 1st approach.

Pls help.

## Your solutions are perfect.

Your solutions are perfect.

As I mentioned in an earlier lesson, plugging in the answer choices is often a great approach. The main problem with that approach, however, is that it can be quite time-consuming for some questions. So, if you can identify an approach that may be faster, you should also consider that.

I should also mention that there are times when we can't plug in the answer choices. For example, if the question asks us to find the SUM of Joe's and Mel's ages, then we can't really do much with the answer choices.

Cheers,

Brent

## https://gre.myprepclub.com/forum

I would like to know why are we not subtracting 3 years from Rolf's current age as it is given in the question? Thanks Brent!

## Question link: https:/

Question link: https://gre.myprepclub.com/forum/meg-is-twice-as-old-as-rolf-but-three-y...

We don't subtract 3 from Rolf's age, because we're told that "three years ago, she was two years older than Rolf is NOW"

Does that help?

Cheers,

Brent

## https://gre.myprepclub.com/forum

Hi Brent!

It's getting little difficult for me to understand this aforementioned question. Could you please help me out?

Thanks,

Ketan

## Hi Ketan,

Hi Ketan,

Here's my full solution: https://gre.myprepclub.com/forum/re-qotd-2-if-1-2-x-years-ago-adam-was-1...

Cheers,

Brent

## Solving from the 4minute mark

## I'm not sure what "x2" is

I'm not sure what "x2" is referring to in your post.

Do you mean to subtract 11 twice from 42?

If so, that would be 20 (not 22..thus my confusion)

Also, we're told that Abbie was 3 times as old as Iris.

So, if Abbie is already 3 times as old as Iris, we cannot make their ages equal by multiplying A (Abbie's age) by 3.

If I'm 3 times as old as you are. We must multiply your age (the younger person) by 3 in order to create an equation.

Does that help?

Cheers,

Brent

## Hi Brent,

I'm having difficulty interpreting the age value, specially in cases when to add or multiply the centered information and how to apply it to each individual.

Like for instance, if someone is "as much as old" as someone else, or if x is n older than y. Hopefully I'm making sense.

what would be a good strategy to be able to overcome this issue.

Thanks

## Let's start with some

Let's start with some fundamentals.

1) If Joe is n years OLDER THAN Sue, then we can write:

(Joe's age) = (Sue's age) + n

2) If Joe is k TIMES AS OLD AS Sue, then we can write:

(Joe's age) = k(Sue's age)

Does that help?

To reinforce these concepts, Keep answering questions from the Reinforcement Activities box.

## Yes it is actually helpful.

So whatever comes after "is" is applied to the 2nd person " in a sense" to make the 2 quantities equal. Is this an accurate conclusion?

## I'm not 100% sure what you're

I'm not 100% sure what you're asking, but I can tell you that IS typically represents "="

Take for example: Joe is n years OLDER THAN Sue

We can first say: Joe's age = n years OLDER THAN Sue

And then say: Joe's age = Sue + n

-----------------------

Another example: Joe is k TIMES AS OLD AS Sue

We can first say: Joe's age = k TIMES Sue's age

And then say: (Joe's age) = k(Sue's age)

Cheers,

Brent

## Very hard question from one

If x/2 years ago Adam was 12, and x/2 years from now, he will be 2x years old, how old will he be 3x years from now?

A 54

B 18

C 24

D 30

E It cannot be determined from the given information.

This is ranked medium? No way! Put it HARD. If only half the people got this question right, it needs to be HARD difficulty. Extremely difficult to understand!

## Question link: https:/

Question link: https://gre.myprepclub.com/forum/re-qotd-2-if-1-2-x-years-ago-adam-was-1...

Keep in mind that, on this site, "medium" is classified as 150-159 (aside: in quant as 159 is a 73rd percentile score).

At the moment, the question has been answered only 8 times, so the sample size may not be large enough to confirm this question is in the 160+ bracket.

I think the level of difficulty is in the high 150's. However, it could very well be in the low 160's.

So, I've changed it to 160-170

Cheers,

Brent

## Hey Brett,

Why do you, at 5:20, when presenting the systems of equations flush with each other, multiply the original equation (A+I)=42 by 3?

## Great question!

Great question!

Let's start with our system:

A + I = 42

A - 3I = -22

When using the elimination method with systems of equations, our goal is to eliminate one of the variables.

Since we have 1A in both equations, I COULD have just subtracted for the bottom equation from the top equation to get: 4I = 64

Solve to get I = 16

However, since the question is asking for the value of A, we still need to plug I = 16 into A + I = 42 in order to find the value of A.

To avoid that last step, I decided to eliminate the terms with variable I (which who would leave me with the variable we're asked to find: A).

To do this, I multiplied both sides of the pop equation by 3 to get:

3A + 3I = 126

A - 3I = -22

Now that we have 3I in both equations, we can ADD the equations to get: 4A = 104

Solve to get: A = 26

As you can see, both methods reach the same conclusion (A = 26).

Both approaches probably take about the same time. I prefer my approach ONLY because it helps me avoid the trap of selecting the wrong answer choice.

If I were to use the first approach and determine that I = 16, I might accidentally conclude that the correct answer is 16 and choose answer choice A.

Isolating the target variable (A in this case) helps me avoid this potential mistake.

Cheers,

Brent

## How does one decide whether

Additionally, how are you able to multiply the top equation in the systems of equations by 3 (A + I=42 becomes 3A+3I=126) after the 5 minute mark?

## Good questions. Here are my

Good questions. Here are my responses:

1) For many word problems, we have the option of assigning one variable or more than one variable. If you assign just 1 variable, the resulting equation will be more complex than the equations you'll create if you assign more than one variable. However, when you assign more than one variable, you end up with a system of equations that can sometimes take longer to solve.

In the video solution above, we used two variables (A and I) to solve the question about Abbie and Iris.

We could have also used just one variable.

For example, we could let A = Abbie's PRESENT age

In that case, 42 - A = Iris' PRESENT age (since their ages add to 42)

So A - 11 = Abbie's age 11 YEARS AGO

And 42 - A - 11 = Iris' age 11 YEARS AGO

....etc.

Our solution is still the same.

For more on how many variables to assign, watch this video: https://www.greenlighttestprep.com/module/gre-word-problems/video/907

2) As long as we perform the same operation to BOTH sides of an equation, the resulting equation will be equivalent to the original equation.

Take, for example, the equation: 2x + 1 = 7 (solution: x = 3)

Add 5 to both sides of the equation to get: 2x + 6 = 12 (solution: x = 3)

Multiply both sides of the original equation by 4 to get: 8x + 4 = 28 (solution: x = 3)

Subtract 11 from both sides of the original equation to get: 2x - 10 = -4 (solution: x = 3)

For more on solving systems of questions, you can watch: https://www.greenlighttestprep.com/module/gre-algebra-and-equation-solvi...

Cheers,

Brent

## How do you know when to

## If we have a system of two

If we have a system of two equations with two variables, we can quickly eliminate one variable (so we can focus on the other variable) if both equations have a coefficient in common.

For example, the equations 2x + 3y = 8 and 2x + y = 4 both have the term 2x.

So if we SUBTRACT the second equation from the first equation, the x terms disappear to get: 2y = 4

Similarly, the equations 2x + 5y = 12 and 4x - 5y = -6 have the term 5y and -5y.

So if we ADD the two equations, the y terms disappear to get: 6x = 6

For more on this strategy, watch the following video (starting at 3:10): https://www.greenlighttestprep.com/module/gre-algebra-and-equation-solvi...

## Why at the 5:03 mark did you

## Good question!!

Good question!!

We have the following system of equations:

A + I = 42

A - 3I = -22

Notice that we have two options:

i) Eliminate the A's and first solve for I.

ii) Eliminate the I's and first solve for A.

Keep in mind that our goal is to solve the system for A.

If we go with option i, then we still have an extra step after solving for I.

That is, once we have the value of I, we must plug it into one of the given equations so that we can solve for A.

On the other hand, if we go with option ii, then we don't have that extra step.

For this reason, I multiplied both sides of the top equation by 3 to get:

3A + 3I = 126

A - 3I = -22

Then I added both equations to get: 4A = 104, which means A = 26

Having said that, I could have also gone with option i.

Let's do that now...

Take:

A + I = 42

A - 3I = -22

Subtract the bottom equation from the top equation to get: 4I = 64, which means I = 16

Now plug I = 16 into the first equation (A + I = 42) to get A + 16 = 42, which means A = 26

So, as you can see, both options work.

## Solid approach for the

Y0: S=M+8

Y4: S= 2M+4

Plugged in option C in 2m+4

12=2m+4 >> M=4

Finally, Y0 S=4+8 = 12

Is this fair approach?

## Great approach!!

Great approach!!